Usability Evaluation of Brazil’s Higher Education Admission System (SiSU): Barriers and Recommendations - Da Costa Nunes, Erik Henrique; Silva, Pedro Victor de Sousa; Souza, Anna Julia Abreu Lima de; Monteiro, Ingrid Teixeira; Vasconcelos, Davi; Yamada, Erika Mayumi Kasai (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC), 2025)
Introduction: This paper reports on a large-scale Usability Test of Brazil’s Unified Admission System (SiSU), conducted in partnership with the Ministry of Education (MEC) with 65 participants (including public school, private school, and university students). Objective: The objective was to evaluate the usability of SiSU and provide recommendations for improving the user experience for the 2026 edition. Methodology: The usability test was a large-scale evaluation of the SiSU system. The test included a group of users performing a set of tasks in a controlled environment. Data was recorded on participants’ performance, opinions, and feelings about their experiences. The study also included an online survey and the User Experience Questionnaire Short Version (UEQ-S) to gather impressions of the system. Results: The results showed an 81% task success rate but revealed recurring issues such as technical jargon, interface inconsistencies, navigation difficulties, and form-flling barriers. Improvement proposals were prioritized based on impact and implementation effort, with numerous recommendations classified as low-effort yet high-impact. The study reinforces the importance of applying Human-Computer Interaction (HCI) methods to enhance inclusive digital public services.